Detection of anti-SARS-CoV-2 salivary antibodies in vaccinated adults - Castro, Vitória Tavares; Chardin, Hélène; Amorim dos Santos, Juliana; Barra, Gustavo Barcelos; Castilho, Grazielle Rodrigues; Souza, Paula Monteiro; Magalhães, Pérola de Oliveira; Acevedo, Ana Carolina; Guerra, Eliete Neves Silva (Frontiers in Immunology, 2023)
This longitudinal study aimed to evaluate the detection of SARS-CoV-2 antibodies in serum and saliva of COVID-19-vaccinated adults. The study included 13 not vaccinated and 35 vaccinated participants with two doses of CoronaVac (Sinovac/Butantan) vaccine who subsequently received BNT162b2 (Pfizer-BioNTech) vaccine as a booster dose. Vaccinated participants donated saliva and serum in three different time points. Enzyme-linked immunosorbent assay was used for antibody detection. In our results, the serum neutralizing antibodies (NAb) were detected in 34/35 samples after second dose and in 35/35 samples one and five months after the booster dose. In saliva, NAb were detected in 30/35 samples after second dose and in 35/35 of samples one and five months after the booster dose. IgA was detected in 19/34 saliva samples after second dose, in 18/35 one month after the booster and in 30/35 five months after. IgG in saliva was detected in 1/34 samples after second dose, 33/35 samples one month after the booster dose and in 20/35 five months after. A strong correlation was found between IgG and neutralizing activity in saliva, and salivary IgA would be a sign of recent exposure to the virus. In conclusion, saliva can be a suitable for monitoring antibodies anti-SARS-CoV-2 after vaccination. Heterologous vaccination contributed to increase anti-SARS-CoV-2 antibodies in the Brazilian health context. Complementary studies with large groups are mandatory to conclude the interest in following mucosal immunity.